Guiding principles for health equity in oncology: insights from patient organizations from the Middle East and Africa - Al-Madhi, Sawsan; Pretorius, Lauren; Shash, Emad; Kurdoglu, Belma; Rabea, Ahmad; Abusanad, Atlal; Nassar, Hani; Kettab, Hamida; Kithaka, Benda; Aziz, Khaled Abdel (Frontiers in Health Services, 2025)
This paper explores the role of patient advocacy in fostering patient-centered care (PCC), empowerment, and equitable access to healthcare in the Middle East and Africa (MEA) region. Despite the vital contributions of patient advisory groups (PAGs) advocating for patients’ rights and helping informed decision-making, implementation of PCC encounters challenges such as cultural variances, language barriers, and general lack of understanding of concepts. A consensus-based Health Equity Steering Committee for the MEA PAG convened a virtual meeting, to identify current practices and gaps in patient-centric approaches in oncology. This discussion highlighted the critical role of collaborations across various sectors to enhance knowledge sharing, access to treatment advancements, and manage societal stigma. A significant gap was observed in data handling by patient organizations, underscoring the need to strengthen data analytics capabilities to improve access programs. Recommendations focused on strengthening collaborations, enhancing data analytics, and integrating patient perspectives into healthcare planning.